Strengthening Generation Z’s Religious Character through Technology-Based Islamic Religious Education Learning - Ade Junaidi Rahmat; Fathullah GZ; Saifuddin; Benny Prasetiya (PT. Education Research Center, 2026)
The development of digital technology has significantly transformed the life and learning patterns of Generation Z, particularly in shaping religious character. Technology offers broad access to information and Islamic learning resources, yet it also creates challenges, including misinformation, social media influence, weak digital religious literacy, and declining internalization of religious values. This study aims to analyze strategies for strengthening the religious character of Generation Z through technology-based Islamic Religious Education (PAI) learning. It employs a literature review method with a qualitative-descriptive approach. Data were collected from relevant national and international journals published between 2021 and 2026 and analyzed using content analysis. The findings indicate that PAI plays a strategic role in developing religious character by integrating Islamic values with digital technology. Effective strategies include the use of Learning Management Systems (LMS), gamification, educational social media, and technology-based Project Based Learning (PjBL). These strategies can be implemented through blended learning, digital mentoring, religious digital content development, and evaluations covering cognitive, affective, and behavioral aspects. This study proposes an integrative model consisting of Islamic value internalization, educational technology use, supportive learning environments, and digital religious habituation to form religious, noble, and adaptive Generation Z learners.